Turismo e pobreza: percepções dos guias de turismo, moradores e não moradores que trabalham na favela da Rocinha Rio de Janeiro - Costa, Augusto Marcelo Alcântara (2013)
This project refers to a study somewhat controversial , as in focusing less recognized and valued hand, although the dynamics of tourism pass to take another view , you can not beforehand consider favorable or unfavorable . Analyzes the phenomenon related to conception or perception of poverty from tourism residents and non residents of the Favela of Rocinha in Rio de Janeiro tourist guides . It is a subject to an object of research somewhat controversial , but about which there is already an academic and scientific concern and deserves an investigator look. Fits as a qualitative study whose methodological procedure based on interviews and participant observation , and the geographic divisions chosen the Rocinha slum , for its expressiveness and for being a pioneer in this type of tourism , had to conducting fieldwork lasting six months, which was accompanied by at least four hours walking work of sixteen tour guides, eight residents and eight non- residents in the community, working for different travel agencies and tourism. End of each tour, all tour guides answered a semi-structured questionnaire, containing nineteen questions. Most respondents tour guides authorized record interview, which has made it possible to analyze the speech through spoken language. In tourism, foreign tourists are the main target, although rarely also count with the participation of domestic tourists. Notes that the relationship between poverty and slums, from the perceptions of tourist guides residents better reflects the reality of favela residents compared with non residents guides, since they fully know all the intricacies and better the difficulties they have endured and still go, when it comes to the issue of stigmatization respect, by which has suffered by Brazilian society, in relation to live in slums, and have your dwelling place as a tourist attraction. While presenting the social reality of Rocinha consistently during his work, the non residents guides worry about being as natural as possible with tourists as much as the locals show slum, in the same way they avoid authorize tourists to take compromising photos and that will expose the intimacy of community residents . Concludes that, while recognizing the importance of elevation to the rank of tourist attraction and its promising prospects, requires attention and priority, given the greater precariousness of the human condition in relation to the prime areas in which it operates tourism should be a vector of development, not a masking of reality